“DEMONIZATION” OF THE ENEMY AS METHOD OF RUSSIAN IMPERIAL PROPAGANDA DURING THE FIRST WORLD WAR - Ruslan Kutsyk; Bohdan Bezpalko (Київські історичні студії, 2020)
The article deals with the main features of creating the negative image of the enemy by the Russian imperial authorities among the population of the Ukrainian lands of the Right Bank of Ukraine in 1914–1917s. The relevance and current state of scientific development of the problem are indicated in the article as well. It is found that during the war, the Russian Empire authorities were aware of high importance specific information campaign as a successful method of struggle. And one of the key areas in this context was connected with the negative image of the Germans and their allies. For this purpose, the authorities, through various mechanisms of informational influence on the society, in practice using of such method of propaganda as “demonization”, whose main task was not simply to form a negative image of the enemy, but to transform it into the plane of religious and dogmatic confrontation of good with evil and the collision of two worlds: Russian as civilized and German as barbaric. The key ideas of the method were: Germany, led by William II, the main culprit of the war; the German army and its allies committed immoral acts, manifested by numerous “atrocities” against civilians and prisoners of war; the Germans and their allies are nothing but absolute evil and the barbarians of the twentieth century, who seek to destroy the civilized world and to enslave free nations. During the war, such theses were not just widespread in society, but became a mass product of the Empire’s propaganda.